Solid acids: potential catalysts for alkene–isoalkane alkylation. Issue 24 (8th November 2017) - Singhal, Shailey; Agarwal, Shilpi; Arora, Shefali; Singhal, Naveen; Kumar, Amit
Abstract : Production of high-octane gasoline is important to improve upon the performance and hence economics of oil companies worldwide. Abstract : Production of high-octane gasoline is important to improve upon the performance and hence economics of oil companies worldwide. Heterogeneous catalysis employing the use of solid acids plays a key role in accomplishing this target through various routes, including isomerization, alkylation, and reforming. Alkylation is an imperative means for this to be achieved in the presence of solid acid catalysts. The use of solid acids as catalysts has been considered as one of the foremost accomplishments in processes of industrial significance in the current century. The introductory part of this review describes the importance of alkylation as a route to obtain high-quality gasoline and the conventional catalysts applied to it globally. The main body of the article details the use of various solid acids as catalysts for alkylation including the concerns about it. It also includes the solution for the drawbacks associated with their use as catalysts for the process. The final section covers the mechanistic approach for alkylation to happen during the progression of the reaction and the recommendations. This review intends to provide a detailed insight into the significance of solid acid catalysts for such an important reaction for chemists, researchers and scientists of refineries.